Large-scale hierarchical oxide nanostructures for high-performance electrocatalytic water splitting. (May 2017) - Ou, Gang; Fan, Peixun; Zhang, Hongjun; Huang, Kai; Yang, Cheng; Yu, Wen; Wei, Hehe; Zhong, Minlin; Wu, Hui; Li, Yadong
Abstract: There is a growing interest in oxide nanocrystal based electrocatalysts for overall water splitting. Despite tremendous efforts, large-scale fabrication of highly-active and durable oxide electrocatalytic electrodes remains as a great challenge. Herein, we report a fast and general strategy for manufacturing a series of hierarchical nanostructured metal oxides (MOx, M= Ti, Mn, Fe, Co, Ni, Cu, Mo, Ag, Sn, W and NiFe) as electrocatalysts by laser ablation on corresponding metal substrates. Particularly, the NiO nanocrystal electrocatalysts (~3 nm) grown on Ni plates have been directly employed as highly active and stable bifunctional electrodes for both hydrogen evolution and oxygen evolution reactions, by taking advantage of its large surface area, rich defects, high hydrophilicity and aerophobicity. The facile laser treatments to construct nanoporous electrodes should facilitate the development of low-cost and high-performance electrocatalytic overall water splitting with large-scale. Graphical abstract: The NiO/Ni plates with hierarchical nanostructures can be synthesized by a fast and general laser ablation process and directly employed as highly active and stable bifunctional electrodes for large-scale overall water splitting. Highlights: The NiO hierarchical nanostructures grown on Ni plate as high performance bi-functional electrocatalysts is demonstrated. Large-scale NiO/Ni electrode can be synthesized by laser ablation within short time and directly used for high efficient water splitting. A series of hierarchical nanostructured metal oxides (MOx, M= Ti, Mn, Fe, Co, Ni, Cu, Mo, Ag, Sn, W and NiFe) have been successfully synthesized by the generalized and fast laser ablation process.